Analisis Tokoh Utama “Sultan Haji” Pada Naskah “Surosowan Burak” karya Toto St Radik - Saiyah, siti; Permanasari, Alis Triena; Roekmana, Giri Mustika (Pendidikan Seni Pertunjukan Fakultas Keguruan dan Ilmu Pendidikan Universitas Sultan Ageng, 2022)
Characters are divided into several types, namely the main character or central character and supporting characters. Every character must have a character or character which is also called characterization. Characterization is the author's way of presenting the characters in the story so that the character or nature of the characters can be known. The research method used is descriptive qualitative research method, a research conducted through an approach that emphasizes the researcher as a key research instrument that plans, implements, collects data, draws conclusions and compiling a complete and systematic research report. There are four scenes in Toto St Radik's